Effects of human presence on the long‐term trends of migrant and resident shorebirds: evidence of local population declines. (4th June 2014) - Martín, B.; Delgado, S.; de la Cruz, A.; Tirado, S.; Ferrer, M.
Abstract This study examines the responses to human presence of the most abundant shorebird species in an important coastal migration staging area (Los Lances Beach, southern Spain). Long‐term census data were used to assess the relationship between bird abundances and human densities and to determine population trends. In addition, changes in individual bird behaviour in relation to human presence were evaluated by direct observation of a shorebird resident species. Our results show that a rapid increase in the recreational use of the study area in summer has dramatically reduced the number of shorebirds and gulls which occur, limiting the capacity of the site as a post‐breeding stop‐over area. In addition, the presence of people at the beach significantly reduced the time that resident species spent consuming prey. Negative effects of human presence on bird abundance remain constant over the study period, showing no habituation to human disturbance in any of the studied species. Moreover, although intense human disturbance at Los Lances Beach occurs mainly in summer, the human presence observed is sufficient to have a negative impact on the long‐term trends of a resident shorebird species. The impacts of disturbance detected on shorebirds and gulls may be reversible through management actions that decrease human presence. We suggest a minimum distance of 80 m for any track or walkway from those areas where shorebirds are usually present, particularly during spring and summer, as well as an appropriate fencing in the most sensitive area.